Meningkatkan Disposisi Berpikir Kritis Belajar Matematika Siswa dengan Menggunakan Model Pembelajaran Problem Based Learning di Kelas XI SMA Negeri 1 Lingsar - Agustina Anggraeni; Masjudin; Sanapiah (Lembaga Pusat Kegiatan Belajar Masyarakat (PKBM) Tunas Harapan, 2025)
This research aims to describe the use of the problem based learning model in improving students' critical thinking disposition in mathematics in class XI at SMAN 1 Lingsar. The type of research used by researchers is Classroom Action Research (PTK) which has four stages, namely planning, implementation, observation and reflection. The subjects of this research are students in class XI IPA 3, totaling 35 students, consisting of 20 male students and 15 female students. . This research instrument uses evaluation sheets and observation sheets of teacher and student activities. The data collection technique in this research is by providing evaluation tests and classroom observations. The research results showed that the average student critical thinking disposition test results in cycle I was 76.90 and the average in cycle II was 78.6. Meanwhile, the percentage of classical completeness achieved in cycle I was 57.14% and the percentage of classical completeness in cycle II was 60%. From the detailed data for each cycle, it can be concluded that the critical thinking disposition with the application of the PBL model experienced a slight and significant increase.